2017
DOI: 10.3762/bjoc.13.73
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-flow processes for the catalytic partial hydrogenation reaction of alkynes

Abstract: The catalytic partial hydrogenation of substituted alkynes to alkenes is a process of high importance in the manufacture of several market chemicals. The present paper shortly reviews the heterogeneous catalytic systems engineered for this reaction under continuous flow and in the liquid phase. The main contributions appeared in the literature from 1997 up to August 2016 are discussed in terms of reactor design. A comparison with batch and industrial processes is provided whenever possible. 734

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 185 publications
(247 reference statements)
0
28
0
Order By: Relevance
“…Isolation of the active sites and electronic effects can be introduced into the catalyst by adding a second metal such as Pb, Au, Cu [60][61][62][63][64][65]. We have decided to investigate the effect of the addition of Bi because it preferentially adsorbs on the step and edge sites of Pd [35,36].…”
Section: Poisoning With Bismuthmentioning
confidence: 99%
“…Isolation of the active sites and electronic effects can be introduced into the catalyst by adding a second metal such as Pb, Au, Cu [60][61][62][63][64][65]. We have decided to investigate the effect of the addition of Bi because it preferentially adsorbs on the step and edge sites of Pd [35,36].…”
Section: Poisoning With Bismuthmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Among them, hydrogenation reactions catalyzed under heterogeneous regime have attracted the interest of several groups, generally grafting the catalysts on solid supports. [9][10][11][12][13] Pérez-Ramírez et al reported the semihydrogenation reaction of alkynes and the reduction of nitro-aromatic substrates using colloidal PtNPs and PdNPs capped by HHDMA (hexadecyl (2-hydroxyethyl) dimethylammonium dihydrogen phosphate) supported on carbon, titanium sulfide, and mesoporous graphite. [14][15][16] The substrate was pumped through the micro-reactor containing the catalyst bed, using an HPLC pump, together with hydrogen generated in situ by an electrolytic cell.…”
Section: Introductionmentioning
confidence: 99%
“…Common reactors for multiphase catalytic reactions include stirred tank reactors (STR), packed/trickle bed reactors, bubble columns, and recently, microreactors where the catalyst is either stationary, eg in packed beds and microreactors, or mobile, eg in stirred tank reactors (STR). There are generally two modes of operation in terms of hydrogen supply, namely continuous gas flow, or gas‐on‐demand . In the former, hydrogen gas is pumped into the reactor continuously, which is generally termed as the open mode of operation.…”
Section: Introductionmentioning
confidence: 99%